An assessment of visitors' perception of Sama Jaya nature reserve Kuching - Kueh, Hsiao Chin (Universiti Malaysia Sarawak (UNIMAS), 2009)
je, first multi-purpose urban forest park in Sarawak, Malaysia, Sama Jaya Nature rve (SJNR) Park covers an area of approximately 38 hectares within the boundary of Kuching City. The forest park is covered with heath forest, patches of peat forest and a few areas of primary forest, which are rich in flora and fauna. It provides various types of recreational activities in a forest setting, different types of museum (e. g., Timber and Bamboo Museum and Forest Biology Museum) displaying a variety of timber specimens, collections of bamboo artifacts, insects, mushrooms as well as forest organisms. The park provides a good recreational opportunity for the public, including individuals and families, like jogging and cycling tracks, foot reflexology, nature study and photography. ) As a result of the increasing impact of recreation on natural resources and visitors' experiences, wilderness managers often want to control recreational use. However, most of them suffer in their attempts to manage wilderness recreational use patterns, as they lack the knowledge of visitors' behaviour in which they seek to influence. In many cases, the concerns of managers towards resource protection do not match visitors' interests, whereas their respective priorities interact with differences in training, education and behavioural norms. This study is thus, carried out to assess visitors' perception towards the SJNR on recreation, education and conservation, as well as their opinion regarding the existing facilities via interview and questionnaire survey. It is also aimed to observe what visitors perceive as being beneficial to them after their visits. The survey was carried out in order to get a more general picture on the level of satisfaction of visitors with the park and their experiences there. Even though the survey covers only a small sample of visitors, it gives an indication of the kinds of people using the reserve and their activities. A total of 80 respondents were covered in the study, where 70 of them were Sarawakian and the rest (10) were non- Sarawakian. Majority of the respondents were from the younger generation. The number of male visitors is higher compared to female visitors, which is 54 and 26 respectively. In addition, Chinese visitors consisted nearly 50% of the total surveyed respondents, while the rest were Malay, Iban, Bidayuh, Kedayan and Murut. Majority of the visitors (40%) interviewed mentioned that they visited the park more than twice a month. Although every visitor has different motives for visiting the park, the main intention of the respondents were for exercising, such as jogging, physical workout and foot reflexology. Over three quarters (83%) of visitors spent one hour or more in the park. From the recreation aspect, majority of the respondents felt that the park provided them with a relaxed atmosphere and made them feel close to nature. They could spend quality time with their family and friends. The survey result also shows that most of the respondents were satisfied with the facilities provided in the park. However, some were not satisfied with the toilets' facility and its cleanliness. From the educational aspect, the respondents stated that they have gained better understanding with regards to the various types of wildlife (e. g., flora and fauna), plant species (e. g., timber, mushroom and bamboo) and insect species after their visit to the museums. In addition, they were also aware of the importance of nature and biodiversity conservation. From the conservational aspect, most of the respondents agreed that they have learned about endangered wildlife species and are also alert on the need to protect and conserve those species. Overall, they were satisfied with the museum exhibitions. The result of the Pearson Correlation, T-test and ANOVA test shows that visitors' demographic background (e. g., gender, age, race and educational level) does not have any significant relation with their perceptions on recreation, education and conservation aspects of the park. Hence, visitors of different background and experiences have their own ideas and views regarding the forest park. With regards to the park's entrance fee of RMO. 50 per entry, most of the respondents (96.3%) felt that it is reasonable. However, a few of them, especially senior citizens and retirees disagree to the fee because it is a burden for them to pay each time they visit the park. Thus, they requested that they are allowed to enter the park free-of-charge. From the Pearson Correlation Analysis, age category was significantly correlated to the perception on entrance fee. This shows that younger generations and middle-aged respondents accepted the entrance fee charges, but the older generations disagree with the fee. In general, nearly all of the respondents (76/80) were satisfied and pleased with the overall park's facilities and its environment since the forest park could fulfill their needs and expectations. Nonetheless, the respondents also gave their suggestions and comments to improve and maintain the park. These comments may be useful and practical to the park management in terms of improving and making park visits more meaningful and beneficial to visitors in the future.